Forms of Vitality Play in Infancy - Español, Silvia Ana (2014)
In this paper we report a qualitative study based on the constant comparative method to initiate the systematic study of forms of vitality play. This is an unnoticed non-figurative play frame linked to early social play and temporal arts in which child and adult elaborate the dynamics of their own movements and sounds in a repetition-variation form. In the introduction we present the theoretical underpinnings and the sporadic observations we have done in previous studies. Then, by the iterative observations of the recorded material of a longitudinal case study on play during the third year of life, we generated the general category of forms of vitality play and four subcategories of display modes of forms of vitality play (improvised forms of vitality play, ritualized forms of vitality play, forms of vitality play combined with pretend play, and forms of vitality play combined with role playing) which are illustrated with descriptive narratives. We discuss the properties of the developed categories, the limits of the present study, and the need to continue systematizing the research on this playful activity.